Mushroom cultivation: A lucrative agribusiness venture - Ojha, Jitendra; Shukla, Sumit Kumar (Indian Farming, 2023)
Mushroom farming is a potential agri-business venture for employment generation as well as raising the income of the rural poor nowadays. There are four types of mushrooms namely Oyster mushroom (pleurotus spp), Paddy straw mushroom (volvariella spp.), Milky mushroom (calocybe spp) and Button mushroom (agaricus spp.) commonly grown in different seasons in India. Button Mushroom cultivation is prevalent in northern India. Mushroom are dense with thiamine (vitamin-B-1), riboflavin (B-2), niacin, pantothenic acid (B-5), biotin, folic acid, vitamin C, D, A and K. In addition, mushrooms contains nearly 85–90% moisture, 3% protein, 4% carbohydrates, 0.3–0.4% fats and 1% minerals and vitamins. Owing to the above properties it can be treated as future food for the population. It is not only good for health conscious peoples but also create the employment opportunities for rural farmers and women as well.